1982
DOI: 10.1002/mus.880050403
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic yield of quantified electromyography and quantified muscle biopsy in neuromuscular disorders

Abstract: Electromyography (EMG), histology, and histochemistry were related in 264 patients with neuromuscular disorders classified according to history and clinical and other laboratory findings. Electromyography and histological and histochemical abnormalities were divided in specific and nonspecific criteria. Specific histochemical criteria alone identified 28% of neurogenic lesions. Criteria of myopathy, obtained from the pattern of electrical activity during 30% of maximal effort, helped to delineate a myopathy wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
0
4

Year Published

1984
1984
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(91 citation statements)
references
References 67 publications
9
78
0
4
Order By: Relevance
“…The semiquantitative assessment used in this study allows easy comparison with routine daily practice in which semiquantitative techniques are most frequently used. The present study confirms several findings reported previously on EMG abnormalities in myositis [10, 11,16,17,18,19,20,21]. Several conclusions can be drawn that add to the present knowledge on EMG in myositis, keeping the retrospective nature of the study in mind.…”
Section: Discussionsupporting
confidence: 81%
“…The semiquantitative assessment used in this study allows easy comparison with routine daily practice in which semiquantitative techniques are most frequently used. The present study confirms several findings reported previously on EMG abnormalities in myositis [10, 11,16,17,18,19,20,21]. Several conclusions can be drawn that add to the present knowledge on EMG in myositis, keeping the retrospective nature of the study in mind.…”
Section: Discussionsupporting
confidence: 81%
“…The scope of this work was the study of the involvement of the anterior tibial muscle in leprosy and for this reason we did not study other muscles with EMG, even knowing that we could find abnormalities in other muscles, if a complete examination was done. Also, even studying only one muscle, as in this paper, a good correlation can be obtained, according previously published papers 21,32 .…”
Section: Resul Resul Resul Resul Results Ts Ts Ts Tssupporting
confidence: 75%
“…values proposed by Buchthal (10), being considered increased if the deviation was over 20% and diminished if it was under 20%. S) Average voltage of voluntary potentials: identical analysis to the previous potentials was made, but the only potentials considered were those which the positive deflexion peak to highest negative was not above 2C3us; there are no agreement in the literature about the normal values3GCuV to 5uV (32), 1C0..V to 2mV (39), higher than 2mV and lower than 4mV (13), 100 to 2000uV (53), important when it exceeds 60C0uV(S5), some hundreds of uV to under 3mV (56) -• we use the voltages found in normal individuals from our laboratory, which vary from 500 to 3000uV (unpublished data); they were considered increased if above SOOOuV and diminished if under 5C0uV.…”
Section: Methodsmentioning
confidence: 99%